Representation of Madurese Culture in the Novel Tanjung Kemarau: A Literary Anthropology Study - Sri Devi, Maharani; Maslikatin, Titik; Ramadhan Muhamad, Abu Bakar (Social Sciences and Humanities Reviews, 2025)
Background: Literature functions not only as a medium of storytelling but also as a reflective space to explore cultural identity. The Madurese culture, though rich in traditions, values, and philosophical depth, is often represented through reductive stereotypes in mainstream narratives. Such portrayals risk eroding the authentic identity of the community. Aims: This study aims to analyse the structural elements of the novel Tanjung Kemarau by Royyan Julian and uncover representations of Madurese cultural identity through the lens of literary anthropology. Methods: Using a qualitative descriptive method and a literary anthropology framework, the novel was examined through its themes, characters, conflicts, settings, symbols, myths, and embedded philosophical values. Data collection included textual analysis and triangulation with ethnographic sources and expert consultations. Results: The findings reveal that Tanjung Kemarau integrates Madurese cultural elements, such as the value hierarchy of bhuppa', bhâbhu', ghuru, rato, the honour-bound principle potèa tolang è tembhâng potè mata, and community rituals like petik laut and matchmaking. Characters and settings illustrate tensions between traditional values and modern social dynamics. Myths and legends embedded in the narrative reflect a syncretic worldview rooted in ancestral wisdom. Conclusion: Tanjung Kemarau serves as more than a fictional narrative; it becomes a cultural archive that documents, critiques, and symbolically reconstructs Madurese identity. The novel validates literature’s potential as an ethnographic medium to reveal complex social realities and challenge dominant cultural discourses. Through this interdisciplinary approach, the study contributes to cultural preservation and supports culturally responsive literary education in a multicultural context.